2011
DOI: 10.1186/1743-8977-8-36
|View full text |Cite
|
Sign up to set email alerts
|

Shape matters: effects of silver nanospheres and wires on human alveolar epithelial cells

Abstract: BackgroundIn nanotoxicology, the exact role of particle shape, in relation to the composition, on the capacity to induce toxicity is largely unknown. We investigated the toxic and immunotoxic effects of silver wires (length: 1.5 - 25 μm; diameter 100 - 160 nm), spherical silver nanoparticles (30 nm) and silver microparticles (<45 μm) on alveolar epithelial cells (A549).MethodsWires and nanoparticles were synthesized by wet-chemistry methods and extensively characterized. Cell viability and cytotoxicity were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
148
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(170 citation statements)
references
References 39 publications
(52 reference statements)
9
148
1
5
Order By: Relevance
“…1 A wide variety of synthesis techniques and routes make it possible to produce Ag nanoparticles (AgNPs) of controlled size, shape, and surface functionality optimized for specific applications. [2][3][4][5][6][7][8][9][10][11][12][13] Pure AgNPs (Ag p NPs) grown and structured in a variety of ways 14 are used in many applications, although challenges related to uniformity and stability remain. 15 There is growing interest in AgNPs with Au cores (Ag Au NPs) due to the ability to tune or optimize their optical and catalytic behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…1 A wide variety of synthesis techniques and routes make it possible to produce Ag nanoparticles (AgNPs) of controlled size, shape, and surface functionality optimized for specific applications. [2][3][4][5][6][7][8][9][10][11][12][13] Pure AgNPs (Ag p NPs) grown and structured in a variety of ways 14 are used in many applications, although challenges related to uniformity and stability remain. 15 There is growing interest in AgNPs with Au cores (Ag Au NPs) due to the ability to tune or optimize their optical and catalytic behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 More recently, therefore, silver nanoparticles (AgNPs) have been evaluated as a safer alternative to ionic silver. 1,[11][12][13][14][15][16][17][18][19][20] The recent work from our team showed that in comparison with silver, biomolecule-coated, photochemically-produced AgNPs can have both bactericidal and bacteriostatic properties with almost negligible cytotoxic effects. 12 We also showed that oxidation of Ag to AgO is most likely the cause of the cytotoxic effects observed with AgNPs.…”
Section: Introductionmentioning
confidence: 99%
“…super-bugs, bacteria strains (Tenover, 2006), has triggered the search for new, more effective, therapies for bacterial infection control, such as nanoparticulated silver (AgNP) (Varner et al, 2010;Rai et al, 2012;Griffith et al, 2015). Despite some studies suggesting that AgNP can present health risks similar to those of ionic silver (Eckhardt et al, 2013;De Alwis Weerasekera et al, 2015), growing evidence indicates otherwise (Asharani et al, 2008;Travan et al, 2009;Moulton et al, 2010;Trickler et al, 2010;Bouwmeester et al, 2011;Stoehr et al, 2011;Alarcon et al, 2012Alarcon et al, , 2013Lu et al, 2012b;Simpson et al, 2013;Vignoni et al, 2014).…”
Section: Nanomaterials As Therapeutic Agents For Skin Regenerationmentioning
confidence: 99%